PENGARUH BAHAN BAKU DAN PROSES PRODUKSI TERHADAP KINERJA PRODUKSI MINUMAN RASA BUAH PT. NUTRIFOOD INDONESIA - Septian Ripandi; Wiwik Rachmarwi (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
The purpose of this study aims to determine and explain to what extent the influence of raw materials and production processes on the production performance of fruit flavored drinks PT. Nutrifood Indonesia, influence of raw materials and production processes greatly affects production performance, because increased production performance will be able to meet consumer demand for products in the market. Research data analysis using descriptive analysis of the correlation coefficient, multiple linear regression analysis to determine the effect of X1 (Effect of Raw Materials) and X2 (Production Process) on Y (Production Performance). The simultaneous research on the influence of raw materials and production processes has a positive effect on the production performance of PT. Indonesian Nutrifood.